Ureterocele – A case report - Chhetri, PK; Malla, SK (Journal of College of Medical Sciences-Nepal, 2010)
Congenital ureterocele is an uncommon cause of urinary tract obstruction in the young patient. Though they may be diagnosed in utero, some however present in the first few decades of life. Most are associated with a duplex collection system with complete ureteral duplication. Here we report a case of single system ureterocele associated with only a single ureter. Key words: ureterocele; urinary tract obstruction. DOI: 10.3126/jcmsn.v6i2.3615 Journal of college of Medical Sciences-Nepal, 2010, Vol.6, No-2, 38-41